Assisting Student-Athletes in Understanding and Identifying Transferable Skills - Petitpas, Albert; Schwartz, Harriet (My University, 1989)
The concept of transferable skills was defined and an instrument to help student athletes understand and identify their transferable skills was presented. Suggestions for utilization of the instrument for individuals or groups were outlined.
Keywords: skills; career development